Improving the car traffic volume transportation by streamlining the routes - Малахова, Олена Анатоліївна; Шевченко, Олена Вікторівна (Technology audit and production reserves, 2013)
Streamlining the organization system of car traffic volumes at the level of railway network allows optimizing the subunits operation and accelerating the car turnover. It is achieved by establishing rational interaction of train stations and adjacent areas. The tasks of streamlining the transportation routes are related to the NPcomplex problems of combinatorial optimization, which can be solved using the heuristic methods. They do not guarantee an optimal solution, but allow quickly get a solution of appropriate quality and they are the basis for further intellectualization of the transportation process. To create competitive conditions in the service system, there is a need for providing a flexible response of the transportation process technology concerning the users’ requirements to the quality of traffic with guaranteed performance. To this end, it was proposed to select the optimal routes based on the heuristic method of simulated annealing.